Your social network profile reveals you. Issue 1 (18th April 2017) - Sander, Tom; Teh, Phoey Lee; Sloka, Biruta
Abstract : Purpose: This study aims to evaluate the fears of individuals on their profiles' sharing in social network sites (SNSs), regarding its advantages and disadvantages. The researched issues are related with the employment seeking process. The concern of this study is the deviation observation between the fears acquired by the business and private social media members. Design/methodology/approach: This study included an online survey with 236 respondents and calculated indicators of central tendency or location parameter, correlation coefficients and performed analysis of variance. Findings: The result indicated and revealed the hidden danger and opportunities among social network members' profile. This result addressed the need to consider the issue of user's fears in reengineering the practical use of SNSs by organisations. Research limitations/implications: Interesting for further research would be to transfer this research from the employment seeking process in other research fields to generalise the results more accurately. Originality/value: The contribution to the research field is to compare different SNSs and to explain the reasons to use SNS profiles to support organisations by their decisions for a valuable strategy. This study provides an insight in use and behaviour of SNS members that support researchers to understand the behaviour of SNS members regarding their profile under consideration of the employment seeking process.